Mitz : the marmoset of Bloomsbury - Nunez, Sigrid (Soft Skull, 2019)
By 2018 National Book Award-winning author Sigrid Nunez, Mitz is an intimate portrait of the life and marriage of Leonard and Virginia Woolf, as refracted through their small, sickly, pampered, affectionate pet marmoset, Mitz.